Sosialisasi Absensi Berbasis Web Pada Siswa PKL di LKP Pelita Media - Nur Anisah; Mahesa Rahmat; Khairul Shaleh; Reza Ayu Winata (PT. Hasba Edukasi Mandiri, 2025)
Web-based attendance system implementation at LKP Pelita Media represents a significant technological advancement in managing student attendance during their practical work experience (PKL). This study focuses on the development and socialization of a web-based attendance system that replaces the traditional manual recording method. The system features two user levels: instructors and students, with distinct functionalities for each. Instructors can manage student data, monitor attendance, and handle notes, while students can independently record their attendance and submit notes. The implementation process included system development, socialization, and training phases. The results show that this digital transformation has improved operational efficiency, data accuracy, and attendance management at LKP Pelita Media. This modernization demonstrates the successful integration of information technology in educational institutions to meet contemporary needs.